EVALUASI PEMANFAATAN BANTUAN PEMERINTAH PADA KELOMPOK BUDIDAYA IKAN (POKDAKAN) DI KOTA SAMARINDA (Evaluation Of The Utilization Of Government Assistance In Fish Cultivation Group In Samarinda City) - JULIANI - JULIANI; HENNY - PAGORAY; HENRIECO DWINTARA TEGUH PRAMUDA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2022)
The fish cultivation group (Pokdakan) in Samarinda City in carrying out fish cultivation business is a home industry or in a small scale business with a source of funds from group members. The purpose of this study is to formulate strategies and concepts for the management of the use of government assistance in fish farming groups in Samarinda City, and determine priority policies for the use of government assistance in fish farming groups in Samarinda City. This research was conducted from October 2021 to March 2022 in Samarinda City. Determination of the number of samples using purposive sampling method, using SWOT analysis and QSPM Matrix (Quantitative Strategic Planning Matrix). The results show that the results of the evaluation of fish farming groups in the assistance program that formulate strategies and concepts for the use of assistance from the government are still needed and needed by fish farming groups in Samarinda City, and the use of assistance that determines priority policies provided by the government for fish farming groups in the City of Samarinda. Samarinda by increasing the knowledge and technical capabilities of fish cultivators in the application of sustainable fish farming technology.